Economic and Social Consequences of Fringe Benefits - Douglas, Monteath (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1960)
SummaryIn this article, the Author analyses fringe benefits as fundamental values. According to him, fringe benefits are more than an increase in the pay check; they are an important and permanent element of wage administration structure.